A Clustered-Based Categorization of Millennials in their Technology Behavior. Issue 3 (7th February 2019) - Calvo-Porral, Cristina; Pesqueira-Sanchez, Rogelio; Faiña Medín, Andrés
ABSTRACT: There is an increasing interest for millennials; however, to date, millennials' segmentations regarding their technology behavior are scarce. This study addresses the following questions: " Are there segments within this generation group regarding their digital technology behavior?" . And if so: " Are there variances in the way that millennial segments use digital technology? "; and further: " What are the main differences among millennial segments regarding their technology behavior? ". Data from a sample of 707 millennials were analyzed through principal components and cluster analysis. Then, millennials' segments were profiled using a multivariate analysis of variance (MANOVA) analysis. Findings revealed that not every millennial has the same technology use and behavior. Moreover, there are five clustered-based segments of millennials regarding their technology behavior: technology devotees, technology spectators, circumspects, technology adverse users, and productivity enhancers . This study contributes with a detailed perspective of how different millennial segments use digital technology.